Charity's burden : a Quaker midwife mystery - Maxwell, Edith (Woodbury, Minnesota : Midnight Ink, 2019)
The winter of 1889 is harsh in Amesbury, Massachusetts, but it doesn't stop Quaker midwife Rose Carroll from making the rounds to her prenant and postpartum mothers. When Charity Skells dies from an apparent early miscarriage, Rose wonders about the symptoms that don't match the stated case of death.
Keywords: Quakers -- Fiction; Midwives -- Fiction; Detective and mystery fiction; Mystery fiction